Deciphering the Prognostic and Predictive Value of Urinary CXCL10 in Kidney Recipients With BK Virus Reactivation - Tinel, Claire; Vermorel, Agathe; Picciotto, Daniela; Morin, Lise; Devresse, Arnaud; Sauvaget, Virginia; Lebreton, Xavier; Aouni, Laïla; Prié, Dominique; Brabant, Séverine; Avettand-Fenoel, Véronique; Scemla, Anne; et al. (Frontiers in Immunology, 2020)
BK virus (BKV) replication increases urinary chemokine C-X-C motif ligand 10 (uCXCL10) levels in kidney transplant recipients (KTRs). Here, we investigated uCXCL10 levels across different stages of BKV replication as a prognostic and predictive marker for functional decline in KTRs after BKV-DNAemia. uCXCL10 was assessed in a cross-sectional study (474 paired urine/blood/biopsy samples and a longitudinal study (1184 samples from 60 KTRs with BKV-DNAemia). uCXCL10 levels gradually increased with urine (P-value <0.0001) and blood BKV viral load (P<0.05) but were similar in the viruria and no BKV groups (P>0.99). In viremic patients, uCXCL10 at biopsy was associated with graft functional decline (HR=1.65, 95% CI [1.08-2.51], P=0.02), irrespective of baseline eGFR, blood viral load or BKVN diagnosis. uCXL10/cr (threshold: 12.86 ng/mmol) discriminated patients with a low risk of graft function decline from high-risk patients (P=0.01). In the longitudinal study, the uCXCL10 and BKV-DNAemia trajectories were superimposable. Stratification using the same uCXCL10/cr threshold at first viremia predicted the subsequent inflammatory response, assessed by time-adjusted uCXCL10/cr AUC (P<0.001), and graft functional decline (P=0.03). In KTRs, uCXCL10 increases in BKV-DNAemia but not in isolated viruria. uCXCL10/cr is a prognostic biomarker of eGFR decrease, and a 12.86 ng/mL threshold predicts higher inflammatory burdens and poor renal outcomes.